Nonmonotonous temperature dependence of Shapiro steps in YBCO grain boundary junctions - Revin, Leonid S.; Masterov, Dmitriy V.; Parafin, Alexey E.; Pavlov, Sergey A.; Pankratov, Andrey L. (Beilstein Journal of Nanotechnology, 2021)
The amplitudes of the first Shapiro steps for an external signal with frequencies of 72 and 265 GHz are measured as function of the temperature from 20 to 80 K for a 6 μm Josephson grain boundary junction fabricated by YBaCuO film deposition on an yttria-stabilized zirconia bicrystal substrate. Non-monotonic dependences of step heights for different external signal frequencies were found in the limit of a weak driving signal, with the maxima occurring at different points as function of the temperature. The step heights are in agreement with the calculations based on the resistively–capacitively shunted junction model and Bessel theory. The emergence of the receiving optima is explained by the mutual influence of the varying critical current and the characteristic frequency.
Keywords: characteristic frequency; Shapiro steps; temperature dependence; YBaCuO Josephson junction